Aging and chronic administration of serotonin-selective reuptake inhibitor citalopram upregulate Sirt4 gene expression in the preoptic area of male mice - Dutt Way, Wong; Soga, Tomoko; Parhar, Ishwar S. (Frontiers in Genetics, 2015)
Sexual dysfunction and cognitive deficits are markers of the ageing process. Mammalian sirtuins (SIRT), encoded by sirt 1-7 genes, are known as ageing molecules which are sensitive to serotonin (5-hydroxytryptamine, 5-HT). Whether the 5-HT system regulates SIRT in the preoptic area (POA), which could affect reproduction and cognition has not been examined. Therefore, this study was designed to examine the effects of citalopram (CIT, 10mg/kg for 4 weeks, wk), a potent selective-serotonin reuptake inhibitor and ageing on SIRT expression in the POA of male mice using real-time PCR and immunocytochemistry. Age-related increases of sirt1, sirt4, sirt5, and sirt7 mRNA levels were observed in the POA of 52 wk old mice. Furthermore, 4 wk of chronic CIT treatment started at 8 wk of age also increased sirt2 and sirt4 mRNA expression in the POA. Moreover, the number of SIRT4 immuno-reactive neurons increased with ageing in the medial septum area (12 wk = 1.00±0.15 vs 36 wk = 1.68±0.14 vs 52 wk = 1.54±0.11, p<0.05). In contrast, the number of sirt4-immunopositive cells did not show a statistically significant change with CIT treatment, suggesting that the increase in sirt4 mRNA levels may occur in cells in which sirt4 is already being expressed. Taken together, these studies suggest that CIT treatment and the process of ageing utilize the serotonergic system to up-regulate SIRT4 in the POA as a common pathway to deregulate social cognitive and reproductive functions.